Critical Reexamination of the Event of the Splitting of the Moon in Light of the Noble Qur'an - Al-Mohammad, Seyyed Taghi; Nayini, Nahleh Gharoavi (Universitas Muhammadiyah Surakarta, 2025)
In Islamic heritage, three perspectives are presented regarding the incident of the moon splitting (Inshiqaq al-Qamar). Two of these perspectives affirm the event as a miraculous sign supporting the prophethood of Muhammad (PBUH), a view supported by most Islamic scholars. On the other hand, the rationalist minority considers the incident as a symbolic reference to apocalyptic signs linked to the Day of Judgment. This study adopts a comprehensive and impartial approach to analyze the arguments of both sides. Ultimately, it supports a purely Qur'anic perspective, identifying the moon splitting as synonymous with the